Professional and under-20 rugby league players improve lower body strength and power at different stage of a rugby league season - Wade, J.; Fuller, J.; Devlin, P.; Doyle, T. (Journal of Australian Strength and Conditioning, 2018)
Practitioners should seek to improve strength and power for professional rugby league players during pre-season, and maintain these qualities in-season, strength and power should be prioritised throughout the entire season for under-20 players.